Outcome of adolescents and young adults with acute myeloid leukemia treated on COG trials compared to CALGB and SWOG trials. Issue 23 (19th September 2013) - Woods, William G.; Franklin, Anna R. K.; Alonzo, Todd A.; Gerbing, Robert B.; Donohue, Kathleen A.; Othus, Megan; Horan, John; Appelbaum, Frederick R.; Estey, Elihu H.; Bloomfield, Clara D.; Larson, Richard A.
Abstract : BACKGROUND: A retrospective meta‐analysis of adolescents and young adults (AYAs) with acute myeloid leukemia (AML) was performed to determine if differences in outcome exist following treatment on pediatric versus adult oncology treatment regimens. METHODS: Outcomes were compared of 517 AYAs with AML aged 16 to 21 years who were treated on Children's Oncology Group (COG), Cancer and Leukemia Group B (CALGB), and Southwest Oncology Group (SWOG) frontline AML trials from 1986 to 2008. RESULTS: There was a significant age difference between AYA cohorts in the COG, CALGB, and SWOG trials (median, 17.2 versus 20.1 versus 19.8 years, P  < .001). The 10‐year event‐free survival of the COG cohort was superior to the combined adult cohorts (38% ± 6% versus 23% ± 6%, log‐rank P  = .006) as was overall survival (45% ± 6% versus 34% ± 7%), with a 10‐year estimate comparison of P  = .026. However, the younger age of the COG cohort is confounding, with all patients aged 16 to 18 years doing better than those aged 19 to 21 years. Although the 10‐year relapse rate was lower for the COG patients (29% ± 6% versus 57% ± 8%, Gray's P  < .001), this was offset by a higher postremission treatment‐related mortality of 26% ± 6% versus 12% ± 6% (Gray's P  < .001). Significant improvements in 10‐year event‐free survival and overall survival were observed for the entire cohort in later studies. CONCLUSIONS: Patients treated on pediatric trials had better outcomes than those treated on adult trials, but age is a major confounding variable, making it difficult to compare outcomes by cooperative group. Cancer 2013 ;119:4170–4179. © 2013 American Cancer Society . Abstract : Adolescent and young adults with acute myeloid leukemia had equivalent outcomes whether treated on pediatric or adult trials when factoring in age. Pediatric trials led to significantly lower relapse rates as well as higher treatment‐related mortality.